Enhancing Students’ Critical Thinking Skills: A Quasi-Experiment Study on Inquiry Learning Model - Femmy Roosje Kawuwung; Jimmi Andrew Mamahit; Nidal Jabari (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Limitations of innovation in learning can cause problems, including the low critical thinking skills of students. Critical thinking skills are important in problem-solving activities, innovating, and being able to make decisions. Students’ critical thinking skills can be improved through the inquiry learning model that focuses on finding new information or knowledge. This study aims to analyze the effect of the inquiry learning model on students’ critical thinking skills using quasi-experimental research with research on the static-group comparison design. Data were collected from pre-research data (to determine the initial ability of students’ critical thinking skills before treatment), pre-test, and post-test based on indicators of critical thinking skills. Statistical data were analyzed using prerequisite tests of normality test (Kolmogorov-Smirnov test), paired sample t-test (if the data is normal), homogeneity test (Levene’s test), and the difference of critical thinking skills were measured using the independent sample t-test (if the data is normal) with SPSS. The results of the data analysis showed significant differences in the critical thinking skills of students participating in the inquiry learning model and conventional learning.